Transcriptome and biochemical analyses revealed a detailed proanthocyanidin biosynthesis pathway in brown cotton fiber. - Yue-Hua Xiao (Public Library of Science (PLoS), 2014)
Brown cotton fiber is the major raw material for colored cotton industry. Previous studies have showed that the brown pigments in cotton fiber belong to proanthocyanidins (PAs). To clarify the details of PA biosynthesis pathway in brown cotton fiber, gene expression profiles in developing brown and white fibers were compared via digital gene expression profiling and qRT-PCR. Compared to white cotton fiber, all steps from phenylalanine to PA monomers (flavan-3-ols) were significantly up-regulated in brown fiber. Liquid chromatography mass spectrometry analyses showed that most of free flavan-3-ols in brown fiber were in 2, 3-trans form (gallocatechin and catechin), and the main units of polymeric PAs were trihydroxylated on B ring. Consistent with monomeric composition, the transcript levels of flavonoid 3', 5'-hydroxylase and leucoanthocyanidin reductase in cotton fiber were much higher than their competing enzymes acting on the same substrates (dihydroflavonol 4-reductase and anthocyanidin synthase, respectively). Taken together, our data revealed a detailed PA biosynthesis pathway wholly activated in brown cotton fiber, and demonstrated that flavonoid 3', 5'-hydroxylase and leucoanthocyanidin reductase represented the primary flow of PA biosynthesis in cotton fiber.